Immediate 2-Stage breast reconstruction outcomes after proton or photon postmastectomy radiotherapy - Robert W. Gao; William S. Harmsen; Na L. Smith; Trey C. Mullikin; Adam C. Amundson; Feven Abraha; Kimberly G. Gergelis; Arslan Afzal; Christin A. Harless; Aparna Vijayasekaran; Minh-Doan T. Nguyen; Judy C. Boughey; et al. (Clinical and Translational Radiation Oncology, 2025)
Purpose: To evaluate the impact of postmastectomy radiotherapy (PMRT) on immediate breast reconstruction (IBR) outcomes among patients treated with proton or photon radiotherapy. Material and Methods: Patients who had undergone mastectomy, immediate breast reconstruction, and PMRT at our institution were included in a retrospective analysis of risk factors for surgical site infection (SSI), unplanned reoperation, and reconstruction failure. Univariate Cox models were used to examine associations of variables with reconstruction outcomes. Results: Two-hundred thirty-one women were included, of whom 224 (97.0 %) underwent two-stage IBR with placement of a tissue expander and 7 (3 %) had direct-to-implant IBR. One-hundred sixty-five patients (71.4 %) received proton and 65 (28.6 %) received photon therapy. Twenty-nine patients (12.6 %) received hypofractionation. Median follow-up was 1.8 years. Two-year cumulative risk of SSI was 17.83 % (95 % CI 12.27–24.41 %); unplanned reoperation was 16.19 % (95 % CI 10.06–22.10 %); and reconstruction failure was 7.60 % (95 % CI 3.55–12.11). On multivariable analysis, prophylactic use of Mepitel Film reduced the risk of SSI [HR: 0.35 (95 % CI: 0.18–0.69), p = 0.002] and unplanned reoperation [HR: 0.39 (95 % CI: 0.20–0.79), p = 0.008]. The small number of events (n = 16) precluded multivariable analysis of reconstruction failure; on univariate analysis, receipt of a chest wall boost [HR: 4.98 (95 % CI: 1.12–22.10), p = 0.035] and/or lymph node boost [HR: 3.66 (95 % CI: 1.25–10.73), p = 0.018] were associated with reconstruction failure. Conclusions: Although approximately one-fifth of women experienced SSI or unplanned reoperation, the rate of reconstruction failure was low (7.6%) and most women achieved a successful reconstruction outcome with PMRT using photons or protons. The lower rate of SSI and unplanned reoperation with use of Mepitel Film highlights the need for further evaluation.